The co-operative rating system and the internal management factors influencing the performance of cooperatives in Sabah, Malaysia: an exploratory study / Sharon Cheuk - Cheuk, Sharon (Universiti Teknologi MARA Cawangan Selangor, 2012)
This paper describes an exploratory study into the co-operative rating system of Suruhanjaya Koperasi Malaysia (SKM), and the internal management factors influencing the performance of co-operatives in Sabah, Malaysia, as identified by the SKM. Secondary documents review and interviews with SKM officials were employed to discover the formal rating process executed by SKM. A survey was also conducted on 101 finance officials of Sabah co-operatives on their awareness level of the financially-relevant circulars/guidelines issued by SKM and their own assessment of their co-operatives, based on the identified internal management factors. The SKM rating process is then described. Survey results indicated that officials were largely not familiar with the financially-relevant SKM circulars/guidelines, and had a neutral/positive assessment of their co-operatives' capital and financial position, liquidity, general asset position, investments, management, income quality and IT system. A significant number were neutral/agreed that the collectibility of members' accumulated loans could be doubtful.